Do placebos alter sleep?. Issue 6003 (24th January 1976) - Adam, K; Adamson, L; Brezinová, V; Oswald, I
Abstract : Deliberate suggestion that an inert capsule was a sleeping pill was found not to influence subjective ratings of sleep quality or anxiety or the electrophysiologically recorded features of sleep in 10 volunteers aged 41-62 years.